2020
DOI: 10.1155/2020/8895900
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum FAM19A5 with Cognitive Impairment in Vascular Dementia

Abstract: Objective. Family with sequence similarity 19 member A5 (FAM19A5), a novel chemokine-like peptide, is a secreted protein mainly expressed in the brain. FAM19A5 was recently found to be involved in a variety of neurological diseases; however, its correlation with vascular dementia (VaD) remains unclear. The aim of the study is to explore the association between serum FAM19A5 and cognitive impairment in subjects with VaD. Method. 136 VaD subjects and 81 normal controls were recruited in the study. Their demograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…Research Object. We followed the methods of Dr. Juan Li et al [9]. A total of 146 VAD patients admitted to our hospital from February 2015 to February 2020 were selected as the VAD group, including 70 females and 76 males, aged 40-75 years, with an average of 69:75 ± 7:23 years old.…”
Section: Methodsmentioning
confidence: 99%
“…Research Object. We followed the methods of Dr. Juan Li et al [9]. A total of 146 VAD patients admitted to our hospital from February 2015 to February 2020 were selected as the VAD group, including 70 females and 76 males, aged 40-75 years, with an average of 69:75 ± 7:23 years old.…”
Section: Methodsmentioning
confidence: 99%
“…As people's lifestyle changes and life pressure increases, the prevalence of VaD remains high. The latest epidemiological studies show that the number of people diagnosed with dementia will rapidly increase to 131 million by 2050 [ 5 , 6 ]. Hypertension, diabetes, smoking, hyperlipidemia, and arrhythmia are common causes of VaD [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to statistics from the World Health Organization (WHO), there are cur-rently about 36 million people with dementia in the world. By 2050, this number will reach to 115 million, and VaD accounts for about 20% of them, second only to Alzheimer's disease (AD) [3]. It is reported that the prevalence of VaD in developed countries ranges from 1% to 4%, while the prevalence of VD in developing countries is about 8%, and the prevalence of VD in the elderly is rising rapidly [4].…”
Section: Introductionmentioning
confidence: 99%